1991
DOI: 10.1002/syn.890090405
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical evidence for methamphetamine‐induced serotonergic axon loss in the rat brain

Abstract: Central serotonin (5-HT) axons were visualized by immunocytochemistry to assess both acute and long-lasting changes in innervation density following methamphetamine administration to rats. Two morphologically distinct subtypes of 5-HT axons (fine and beaded) were differentially affected by d-methamphetamine (d-MA); the density of fine serotonergic axons was selectively decreased both 4 hours and 2 weeks after administration of d-MA. Acute depletion of 5-HT from fine axons, but not from beaded axons, was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 24 publications
1
65
0
Order By: Relevance
“…In sufficient doses, mAMPH causes long-term damage to DA terminals in the striatum and to forebrain 5-HT terminals, as evidence by long-term depletions in these two neurotransmitters, their synthetic enzymes, metabolites, and plasma membrane transporters (Koda and Gibb, 1973;Hotchkiss and Gibb, 1980;Schmidt et al, 1985;Wagner et al, 1979;Ricaurte et al, 1982;Axt and Molliver, 1991;Friedman et al, 1998;Chapman et al, 2001). The mAMPH-induced depletions of DA reverse with a very slow time course (Cass and Manning, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In sufficient doses, mAMPH causes long-term damage to DA terminals in the striatum and to forebrain 5-HT terminals, as evidence by long-term depletions in these two neurotransmitters, their synthetic enzymes, metabolites, and plasma membrane transporters (Koda and Gibb, 1973;Hotchkiss and Gibb, 1980;Schmidt et al, 1985;Wagner et al, 1979;Ricaurte et al, 1982;Axt and Molliver, 1991;Friedman et al, 1998;Chapman et al, 2001). The mAMPH-induced depletions of DA reverse with a very slow time course (Cass and Manning, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neurotransmitter immunohistochemistry may augment the interpretation of other biochemical data. This approach has been applied to neurotoxicity evaluations that characterize the loss of serotonin immunoreactivity in adult rats after treatment with drugs known to act on this neurotransmitter system (34,35). These studies have shown not only the loss of serotonin immunoreactivity but also changes in the morphologic appearance of the serotonin nerve terminal network.…”
Section: Stains For Neurotransmitters and Neuron-specific Protein Marmentioning
confidence: 99%
“…Evidence from animal and human studies suggests that long-term exposure or high dosages of amphetamines causes neuronal damage. Anatomical evidence supporting the neurotoxic potential of METH stems from studies showing that a high dose of METH given to rats caused degeneration of dopamine (DA) nerve terminals, and loss of tyrosine hydroxylase (TH), DA transporter (DAT), tryptophan hydroxylase (TPH), and 5-hydroxytryptamine (5-HT) axon terminals (Axt and Molliver, 1991;Gibb et al, 1990;Ricaurte et al, 1982;Seiden and Sabol, 1996). Further support for the neurotoxic potential of METH comes from evidence that (a) high doses of METH cause striatal gliosis as shown by an increase of glial fibrillary acidic protein (GFAP) in rats and mice (Battaglia et al, 2002;O'Callaghan and Miller, 1994;Sheng et al, 1994), and (b) apoptotic pathways are involved in METH-induced neuronal injury .…”
Section: Introductionmentioning
confidence: 99%